Standing on the shoulders of giants: Essential papers in sports and exercise physiology - de Koning, J. J. (International Journal of Sports Physiology and Performance, 2024)
Purpose: The purpose of this survey was to create a list of essential historical and contemporary readings for undergraduate and graduate students in the field of exercise physiology. Methods: Fifty-two exercise physiologists/sport scientists served as referees, and each nominated ~25 papers for inclusion in the list. In total, 396 papers were nominated by the referees. This list was then sent back to the referees, with the instructions to nominate the "100 essential papers in sports and exercise physiology." Results: The referees cast 4722 votes. The 100 papers with the highest number of votes received 51% (2406) of the total number of votes. A total of 37 papers in the list of "100 essential papers" were published >50 years ago, and 63 papers were published since 1973. Conclusions: This list of essential studies will provide a perspective on contemporary studies, the "giant`s shoulders" to enable young scholars to "see further" or to understand where they have "come from." This compilation is also meant to impress on students that, given the (lack of) technology available in the past, some of the early science required enormous intuitive leaps on the part of historical scientists.